Assortative mating for obesity - Speakman, John R; Djafarian, Kurosh; Stewart, Joanne; Jackson, Diane M (The American journal of clinical nutrition, 2007)
BACKGROUND: Assortative mating is the nonrandom mating of individuals with respect to phenotype and cultural factors. Previous studies of assortative mating for obesity have indicated that it may have contributed to the obesity epidemic. However, those studies all used body mass index or skinfold thicknesses to measure obesity and did not always account for potential confounding factors. OBJECTIVE: We aimed to assess the level of assortative mating for obesity by using dual-energy X-ray absorptiometry to characterize body composition. DESIGN: This was a cross-sectional study of 42 couples. RESULTS: Raw spousal correlations showed assortative mating for age, weight, body mass index, lean mass, and fat mass. Removing the effect of age on fat mass strengthened the spousal correlation (r = 0.405). Social homogamy did not appear to be important, because in this sample there was no significant effect of area of origin on age-corrected fat and lean tissue masses for either sex. Regional body-composition analysis showed that subjects with disproportionately large arms (both fat and lean) assortatively mated with partners with the same trait. However, both men and women with high lean tissue in their arms assortatively mated with partners that had a disproportionately low fat content in their legs. CONCLUSIONS: These data confirm that assortative mating for obesity exists when dual-energy X-ray absorptiometry is used to evaluate adiposity. We hypothesize that assortative mating may have contributed to the obesity epidemic because the time course of obesity development has shifted progressively earlier, allowing singles in their late teens and early twenties to more easily distinguish partners with obese and lean phenotypes.